Optimisasi produksi biogas dari limbah lateks cair pekat dengan penambahan logam Optimization of biogas production from concentrated-latex effluent with addition of metals - Irma KRESNAWATY; I SUSANTI; . SISWANTO; . TRI-PANJI (Menara Perkebunan, 2008)
Summary The treatment of concentrated-latex effluent process applied in the field presently, has not obtain optimum additional benefits. Besides that, the technology using ponding system  needs  wide area and causes air pollution that  such a way caused conflicts with society. The application  concept of clean industry: reuse, reduction, recovery and recycling, makes the possibilities to convert the effluent to be usefull products. One of the alternative effluent process is by utilizing it as the source of renewable energy, that is in the form of biogas as an  alternative energy. The preliminary research showed that the use of spontaneous latex skim coagulation, the  addition of 1% manure as source of seed, and leaf biomass as the source of carbon could increase the biogas production. This research was carried out to optimize biogas production by adding metal ion and to observe the parameters which influenced every stage of biogas production. At the beginning of the process, pH showed increasing due to the hydrolysis process that generally occured in acid condition, but it remained stable (6.6-7.7) in the next steps, whereas, the VFA value as well as BOD value tended to increase. COD value had fluctuative inclination caused by the conversion of organic compounds to produce biogas and the hydrolysis process of leaf biomass to organic compounds that decom-posed to further biogas. The best result of biogas production was showed by addition of Fe3+ with optimum concentration 0.50 mg/L effluent.